2020
DOI: 10.1183/23120541.00319-2020
|View full text |Cite
|
Sign up to set email alerts
|

(Oral) enoximone in asthma

Abstract: The Enoximone in status asthmaticus letter [1] referenced our case series from the Netherlands wherein intravenous enoximone (Perfan, Carinopharm, Germany) reversed status asthmaticus in eight patients [2]. SCHULZ et al. [1] end their letter with the statement that further research is called for; this correspondence is to indicate that research has been carried out and is still ongoing. Recently, SOBHY et al. [3] confirmed our case series with a successful clinical trial, which was performed in Egypt, using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…These patients received a maximum oral daily dose of 25 mg enoximone in a customized fashion (i.e., once daily or less) without noticeable side effects. 16 At the currently applied dosing regimen, enoximone was well-tolerated on top of other medications and, as expected given no reported interactions or contraindications, no clinically relevant adverse events were noted.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…These patients received a maximum oral daily dose of 25 mg enoximone in a customized fashion (i.e., once daily or less) without noticeable side effects. 16 At the currently applied dosing regimen, enoximone was well-tolerated on top of other medications and, as expected given no reported interactions or contraindications, no clinically relevant adverse events were noted.…”
Section: Discussionsupporting
confidence: 52%
“…In the presented cases, we applied even lower doses of enoximone based on our experience with oral enoximone in asthma patients (>80 patients and approximately 300 patient years) 16 in an ambulatory setting. These patients received a maximum oral daily dose of 25 mg enoximone in a customized fashion (i.e., once daily or less) without noticeable side effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…46 Also oral enoximone very quickly and significantly improved difficult-to-treat asthma, as well as reduced steroid and β 2 -agonist drugs in 47 out of 51 adult patients, and in 11 of the 12 children. 47 Preclinical data have shown that sildenafil, a selective PDE5 inhibitor that is used extensively in erectile dysfunction in males, inhibits the airway hypersensitivity and leukocyte influx in conscious guinea pigs 48 and could reduce airway inflammation and mucus production in rats. 49 Furthermore, sildenafil and tadalafil, another selective PDE5 inhibitor decreased pro-inflammatory cytokines in serum and BALF and inhibited oxidative and nitrosative stress in a rat model of bronchial asthma.…”
Section: Current Scenario With Selective Pde Inhibitors In Asthmamentioning
confidence: 99%